Working conditions and depression in hospital emergency service nurses - Márcia Regina Guedes Silva; João Fernando Marcolan
ABSTRACT Objective: to analyze the presence, intensity and factors related to working conditions for depressive symptoms in hospital emergency nurses in the east of São Paulo. Methods: a descriptive, exploratory, quantitative and qualitative study, which applied psychometric scales and interview script. Results: nurses (95.24%) had depressive symptoms by the assessment scales by the observer, most with mild and moderate intensity. Inadequate working conditions led to suffering. Factors that trigger depressive symptoms were: disorganized work; harmful relationship with immediate management; inappropriate physician behavior; aggressions; lack of inputs, infrastructure and human resources; professional devaluation. Identified professionals with depressive symptoms who, because they were unaware of being affected by the disorder, did not seek treatment, continued to perform activities that compromised their physical and mental health, promoting damage to the assistance provided. Final considerations: high frequency of depressive symptoms. The precarious work environment negatively influenced the care and development of depressive symptoms.